Technical complex for oil identification - Zaripova Liliya; Shaidakov Vladimir; Barabanov Alexey (E3S Web of Conferences)
The article substantiates a technological complex designed to identify oil transported through pipeline communications. An Azole 7070 marker has been developed, the microdose in the oil of which makes it possible to determine the source of the transported oil. The basic properties of the marker are described. To ensure the injection of small doses of the marker, studies of the working process of the plunger dosing pump were carried out, and a mathematical model was developed. Pulsations of the pumped liquid flow in the valve assembly are noted, which contribute to the disruption of the supply. A process modeling technique has been developed. For mixing the marker with oil, the design of a static mixer with flat mixing elements is justified on the basis of mathematical modeling. Based on the conducted research, a method for modeling the process of mixing liquids has been developed. The technological complex for oil identification, including the Azol 7070 oil marker, a metering pump, and a static mixer, has been successfully tested by the Rosneft oil company and is recommended for implementation.